The Trading Test. - Guizzo, E. (IEEE spectrum)
The financial industry has long been known to hire math whizzes as quantitative analysts, or "quants," who concoct pricing models, probe new ways to quantify risk, and mine data. Now, as automated trading systems take over ever more of the substantive work on Wall Street, many firms are seeking quants who not only know the math but the nuts and bolts of IT systems, too. A big-time financial firm is recruiting tech talent by offering prizes to the college kids whose software chooses the best investments.